PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS VI SDN 004 SIMPANG PULAI KECAMATAN UKUI KEBUPATEN PELALAWAN - Slamet Riyadi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low learning outcomes in Civics (PKn) among students of class VI SDN 004 Desa Simpang Pulai Kecamatan Ukui. Out of 30 students, only 15 completed the PKn learning outcomes, with an average score of 54, where the specified Minimum Completeness Criteria (KKM) is 70.00. The cause of the low learning outcomes is the passivity of students in the learning process. In addition, teachers are still using conventional teaching methods and are teacher-centered. Based on this, the researchers conducted a study to increase learning outcomes through the application of the NHT (Numbered Heads Together) cooperative model. This study is a classroom action research that aims to improve learning outcomes in PKn as well as increase the activity of students in the learning process through the implementation of the NHT type cooperative model. Data collection techniques used were observation of teacher and student activities, achievement tests, and documentation. This study was conducted over two cycles. The data in this research is descriptive, focusing on the activities of teachers and students and learning outcomes in Civics subjects for class VI students. The results of this study showed that the learning outcomes in PKn increased each cycle. Preliminary data states that only 15 students, or 50%, were completed. In the first cycle, mastery learning increased, with 26 students, or 87%, achieving completion. In the second cycle, mastery learning increased again, with 27 students, or 90%, achieving completion.